Bedsided Transcranial Sonographic Monitoring for Expansion and Progression of Subdural Hematoma Compared to Computed Tomography - Niesen, Wolf-Dirk; Rosenkranz, Michael; Weiller, Cornelius (Frontiers in Neurology, 2018)
Introduction: Transcranial high-resolution ultrasonography reliably allows diagnosis and monitoring of intracerebral hemorrhage in adults. Sonographic monitoring of subdural hematoma (SDH) has not been evaluated in adults so far. The present study investigates the reliability of TGS in monitoring acute and chronic SDH in adults. Methods: TGS was performed in 47 consecutive patients with either acute or chronic SDH confirmed by cerebral CT. 4 patients were excluded due to insufficient bone window. After identification of SDH in TGS extent was measured and correlated with extent of SDH on CCT. If possible measurement was performed at least on two days to evaluate the possibility to monitor SDH with TGS. Results: In 43 patients with SDH 76 examinations were performed with two examinations in 23 patients and 3 examinations in 10 patients. Overall extent of SDH correlated significantly between TGS and CCT (r=0.962). Accordingly correlation was high during each single examination time point. In patients in need for surgical evacuation sonographic measurement yielded a sensitivity of 90.9% and specificity of 93.8% in predicting surgical evacuation (p<0.001). Discussion: Imaging of SDH with TGS is possible in patients with SDH and extent of SDH correlates significantly between TGS and CCT during initial as well as during follow-up examination. Thus monitoring of SDH with TGS at patients` bedside is possible.